qanda-logo
apple logogoogle play logo

Calculator search results

Formula
Solve the system of equations
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$6 x - 5 y = 28$
$4 x + 9 y = - 6$
$x$Intercept
$\left ( \dfrac { 14 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , - \dfrac { 28 } { 5 } \right )$
$x$Intercept
$\left ( - \dfrac { 3 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , - \dfrac { 2 } { 3 } \right )$
$\begin{cases} 6x-5y = 28 \\4x+9y = -6 \end{cases}$
$x = 3 , y = - 2$
Solve quadratic equations using the square root
$\begin{cases} 6 x - 5 y = 28 \\ 4 x + 9 y = - 6 \end{cases}$
$ $ Solve a solution to $ x$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 14 } { 3 } } \\ 4 x + 9 y = - 6 \end{cases}$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 14 } { 3 } } \\ \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 9 } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \end{cases}$
$ $ Substitute the given $ x $ value into the equation $ 4 x + 9 y = - 6$
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 14 } { 3 } } \right ) \color{#FF6800}{ + } \color{#FF6800}{ 9 } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 14 } { 3 } } \right ) \color{#FF6800}{ + } \color{#FF6800}{ 9 } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$ $ Solve a solution to $ y$
$\color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$ $ Substitute the given $ y $ value into the equation $ x = \dfrac { 5 } { 6 } y + \dfrac { 14 } { 3 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 14 } { 3 } }$
$x = \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) + \dfrac { 14 } { 3 }$
$ $ Calculate the product of rational numbers $ $
$x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 3 } } + \dfrac { 14 } { 3 }$
$x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 14 } { 3 } }$
$ $ Find the sum or difference of the fractions $ $
$x = \color{#FF6800}{ 3 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ 3 }$
$ $ The possible solutions are as follows $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ 3 } , \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ 3 } , \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$ $ Check if it is the solution to the system of equations $ $
$\begin{cases} \color{#FF6800}{ 6 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = \color{#FF6800}{ 28 } \\ \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 9 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \end{cases}$
$\begin{cases} \color{#FF6800}{ 6 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = \color{#FF6800}{ 28 } \\ \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 9 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \end{cases}$
$ $ Simplify the equality $ $
$\begin{cases} \color{#FF6800}{ 28 } = \color{#FF6800}{ 28 } \\ \color{#FF6800}{ - } \color{#FF6800}{ 6 } = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \end{cases}$
$\begin{cases} \color{#FF6800}{ 28 } = \color{#FF6800}{ 28 } \\ \color{#FF6800}{ - } \color{#FF6800}{ 6 } = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \end{cases}$
$ $ Since it is true in both equations, it is the solution of the system of equations $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ 3 } , \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$ $ 그래프 보기 $ $
Graph
Solution search results
search-thumbnail-$10$ $ \begin{cases} 4x+9y=9 \\ \bar{x} -3y=-6 \end{cases} $
10th-13th grade
Other
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo